Penerapan Asas Legalitas Terhadap Tindak Pidana Korupsi - Kania Nova Ramadhani; Talita Sembiring; Bungana Br. PA; Maulana Ibrahim (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Article 1 paragraph (1) of the Indonesian Criminal Code states the principle of legality in criminal law. This legality principle is a basic principle in the criminal law system that guarantees that a person cannot be punished without a clear legal basis and without going through a fair legal process. This principle also protects individual human rights and prevents abuse of power by the authorities. The purpose of this research is to analyze the application of the Principle of Legality to the crime of corruption and to find out how the application of the principle of legality to the crime of corruption. This research was conducted using the literature study method, which is a method of collecting data by understanding and studying theories from various literatures related to the research. The results of this study indicate that based on the principle of legality as referred to in Article 1 paragraph (1) of the Criminal Code, namely nullapoena sine lege, it means that every criminal sanction must have a legal regulation that regulates it beforehand, the ideal application of the principle of legality in terms of law enforcement for corruption defendants is if the act of corruption can be proven legally and convincingly in a trial that is guided by law enforcement in accordance with the provisions of the applicable legal system contained in the law.